2020
DOI: 10.3390/ijms21113766
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response: Neutron-Induced Therapy Autophagy as a Promising Treatment Option for Osteosarcoma

Abstract: Radiotherapy using high linear energy transfer (LET) radiation results in effectively killing tumor cells while minimizing dose (biological effective) to normal tissues to block toxicity. It is well known that high LET radiation leads to lower cell survival per absorbed dose than low LET radiation. High-linear energy transfer (LET) neutron treatment induces autophagy in tumor cells, but its precise mechanisms in osteosarcoma are unknown. Here, we investigated this mechanism and the underlying signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In cells, the ER is responsible for the proper folding and processing of polypeptide chains into functional proteins. Some exogenous or endogenous factors lead to UPR, which will have a direct impact on tumor proliferation, migration, and apoptosis, and the associations between UPR and ER stress, autophagy, and apoptosis have already been revealed [8]. Several proteins affect the apoptosis and autophagy of cancer cells via UPR-induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cells, the ER is responsible for the proper folding and processing of polypeptide chains into functional proteins. Some exogenous or endogenous factors lead to UPR, which will have a direct impact on tumor proliferation, migration, and apoptosis, and the associations between UPR and ER stress, autophagy, and apoptosis have already been revealed [8]. Several proteins affect the apoptosis and autophagy of cancer cells via UPR-induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The unfolded protein response (UPR) is one of the main mechanisms of tumor cell tolerance to chemotherapeutic drugs [8]. Rapid proliferation leads to an environment consisting of ischemia, hypoxia, and malnutrition in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…ER stress, the UPR, and autophagy are also activated by both high- and low-LET radiation [ 203 , 204 , 217 , 218 ]. The fate of cells following the activation of these pathways depends on the duration and the degree of the response [ 121 , 202 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%
“…The fate of cells following the activation of these pathways depends on the duration and the degree of the response [ 121 , 202 ]. Studies in osteosarcoma and lymphoma cells showed that increased LET induced higher levels of UPR and autophagy [ 139 , 218 ]. ER stress and autophagy were activated by high-LET (I 125 ) radiation in human esophageal squamous cell carcinoma [ 219 ].…”
Section: Signal Transduction By High and Low Letmentioning
confidence: 99%
“…Oh et al further characterized the link between autophagy and radioresistance by means of high linear energy transfer (LET) neutron radiation. Their study noted that high LET neutron radiation led to increased autophagy via inhibition of Akt and downstream mTOR activity [ 49 ].…”
Section: Autophagymentioning
confidence: 99%